Vulnerability Analysis of School Buildings to Tsunami in the Cilacap Coastal Area - Dewa, Hercules Pungky Naga; Nirwansyah, Anang Widhi; Dewi, Ratna Sari; Demirdag, Ismail (Universitas Muhammadiyah Surakarta, 2023)
Cilacap is one of several areas that experienced significant damage due to the Pangandaran tsunami in 2007. Currently, tsunamis are one of the most serious threats to coastal areas as they can cause devastation to the function of coastal areas. The physical environment can extensively affect the probability of damage caused by tsunamis. In addition, it is critical to maintain building stability as a substantial component in the integrated management efforts of coastal areas. The aim of this research is to assess the physical susceptibility and the vulnerability of school buildings to tsunami, particularly senior high school buildings (known as SMA/MA) located in the coastal area of the Cilacap region. This research is essential for the continuity of learning and teaching activities in the coastal area. Therefore, mapping the physical environment and school buildings in the coastal area of the Cilacap region is necessary. In this study, the physical approach method and Papathoma Vulnerability Tsunami Assessment (PVTA) model were optimally applied to assess coastal vulnerabilities to tsunami. Ultimately, the results were further evaluated by using cross-tabulation. The results confirm that specific coastal areas were categorised as having “moderate to high” susceptibility. Simultaneously, owing to the field survey, we determined that school buildings at this location were made of simple reinforced concrete materials. Notwithstanding that the vulnerability of the school buildings were low, the conditions were deemed to be reasonably harmful given that the schools were located in a “moderate to high” susceptibility. The results of this study have implications for the level of potential physical susceptibility of the coastal areas and the vulnerability of school buildings to tsunamis in the Cilacap region.